Factors Associated With Work Fatigue Among Fire Department Officers In Jambi City - Ramadhani Hidayatullah; David Kusmawan; Silvia Mawarti Perdana; Budi Aswin; Ashar Nuzulul Putra (CV. AFDIFAL MAJU BERKAH, 2026)
Work fatigue is an occupational health issue that can reduce productivity, elevate the risk of workplace accidents, and threaten worker safety, particularly in high-risk occupations such as firefighting. This study examined the factors associated with work fatigue among officers of the Jambi City Fire Department, covering age, length of service, body mass index, smoking habits, workload, sleep quality, and heat exposure. A cross-sectional quantitative design was applied, involving all officers who met the inclusion criteria through a total sampling technique, yielding 192 respondents. Data were collected using standardized questionnaires and analyzed through univariate and bivariate chi-Square tests at a significance level of 0.05. The findings showed that 86.5% of respondents experienced a high level of work fatigue. No significant association was found between age (p=0.145), length of service (p=0.099), or body mass index (p=0.509) and work fatigue, whereas smoking behavior (p=0.018; PR=1.163), workload (p=0.025; PR=1.154), sleep quality (p=0.001; PR=1.218), and heat exposure (p=0.019; PR=1.195) were significantly associated with it. These four factors are therefore the main determinants of work fatigue among firefighters, and the institution is expected to design interventions addressing sleep management, workload distribution, smoking-cessation support, and heat-exposure control in the workplace.